Structural reliability of ultra high-performance fibre reinforced concrete beams in flexure. (1st October 2021) - Simwanda, L.; De Koker, N.; Viljoen, C.
Highlights: Experimental UHPFRC beams were numerically modelled using the finite element method and validated against experimental results. FEM moment capacity predictions were systematically higher than analytical predictions based on ACI318, ACI544, and FHWA models. Model factors in the analytical models were calibrated by comparison to stochastic finite element analyses for beams with 1%, 2% and 4% fibre content. Model factors were found to be in the range 1.6 to 1.9, with coefficients of variations of 0.3 to 0.4. Reliability analyses of beams designed according to the analytical models was conducted that incorporate model factors, and reliability values of 3.6 to 4.0 obtained. Abstract: A study of the model uncertainty and structural reliability for ultra high-performance fibre reinforced concrete (UHPFRC) beams under flexure is presented. Model factors are calibrated by comparison to finite element analyses for nine UHPFRC beams with volume percentage of steel fibres in the range of 1–4%, a feasible percentage range to produce UHPFRC. Moment capacity values obtained by the finite element models were systematically higher than values predicted by the analytical models described in ACI-318, ACI-544, and FHWA-HIF-13. The model factors were found to indicate strong positive correlation with the yield stress of steel ( f y ) and strong negative correlation with beam's section geometry ( d / h ). When combined with stochastic descriptions of the remaining parameters that describe these analytical models, reliability values for beams designed to the ACI-318 and ACI-544 specifications are found to be in good agreement with the target values for these standards, while values for FHWA-HIF-13 fall about 15% above this value.